Os bobos do imperador: a tradição picaresca em O chalaça e Era no tempo do rei - Karnikowski, Ulisses Stefanello (2023)
Since its emergence in Renaissance Spain, the picaresque novel has been echoing through increasingly different sounds in contemporary times, distancing itself from the original model, but maintaining some characteristic traces when remodeling them. Thematizing the life of Dom Pedro I, the Brazilian novels O Chalaça (1994), by José Roberto Torero, and Era no Tempo do Rei (2007), by Ruy Castro, are presented as picaresque novels, which instigated us to question whether what form this tradition is being demonstrated in these two novels. To elucidate this investigation, we start from Mikhail Bakhtin's studies about the origins of the novelistic genre, considering the influence of popular laughter in this process and the inclusion of lowered images in Renaissance literature, to which the picaresque novel is inserted. Furthermore, we conducted our research seeking to understand parody, from Linda Hutcheon, a prominent resource in classic picaresque and present in the two analyzed novels. Thus, we realize that both O Chalaça and Era no Tempo do Rei seek to break with the realistic model, using satire and parody to create narrators who move through different times and places of Brazilian society in the Johannine period, revealing the Portuguese Court and historical figures who were close to Dom Pedro. Following the picaresque tradition of fictionalizing popular aspects while demeaning prevailing moral values, both novels make raw social critiques while honoring authors and works that have done so before them. In O Chalaça, the paradigm of classic picaresque is parodied by the narrator's relationship with his master, Dom Pedro, ironizing the masks of a good man necessary for the trickster. In Era no Tempo do Rei, the externally focused narrator makes use of this power to transit through more places, and like a true court jester, he spares no effort to debase the main figures of the Portuguese Court and all figures in the novel. Only Leonardo, the protagonist of Memórias de um Sargento de Milícias, and parodied as a character, is spared, receiving the elevation of carnivalization. The two novels reveal a society intrinsically formed by the mask games of bourgeois anticipated by classical picaresque, as if they saw in Rio de Janeiro in the 19th century the result of this process initiated in the Renaissance. The characters, already used to this movement, allow themselves a mature look at society, revealing habits of those who did not have the desired social ascension and remain culturally marginalized. As neopicares, Leonardo and Chalaça carry on their journey the two poles of Brazilian society at the time, coming from poor families and having Dom Pedro as their best friend, both give a broad panorama of Brazilian society, ranging from the popular to the aristocratic. In short, the two novels give a Brazilian tone to the picaresque tradition, revealing how some masks are necessary to get what you want, especially during Carnival.